Buddhist-Inspired Mindful Practices and Learning Effectiveness among Postgraduate Management Students in Higher Education Institutions - Tripathi, Bijay Kumar; Khanal, Namdev (Lumbini Journal of Language and Literature, 2026)
This research investigates how Buddhist-Inspired Mindful Practices which include: Mindful Awareness, Right Intention, Right Effort, Compassion and Wisdom influence Learning Effectiveness among postgraduate management students in Butwal Sub-metropolitan City, Nepal. A quantitative design, cross-sectional design was used. A structured questionnaire comprising of thirty questions on a five-point Likert scale was used to collect data. A census method was used and 420 questionnaires were administered to get 412 responses. Partial Least Squares Structural Equation Modeling with bootstrapping was used to test reliability, validity, model fit and hypotheses. The findings revealed that Buddhist-Inspired Mindful Practices is very important in boosting Learning Effectiveness. Likewise, among the five dimensions of BIMP, the strongest contributors were Mindful Awareness and Right Effort which were followed by Wisdom, Right Intention and Compassion. The model demonstrates power of prediction, which proves that these inner potentials contribute towards acts of concentration, perseverance, emotional control, and significant scholastic interaction. The study proves Buddhist-oriented model of mindfulness in universities and suggests that higher education must integrate mindful practices in education, curriculum and student progress to promote overall scholastic and individual well-being.